Penuaan Kardiovaskular: Tinjauan Sistematis atas Perubahan Struktural, Fungsional, dan Molekuler - Sidhi Laksono Purwowiyoto; Wella Widyani (Jurnal Kesehatan Indonesia, 2026)
Background: Aging is a progressive biological process that affects the structure, function, and molecular regulation of the cardiovascular system. These changes increase the risk of heart disease, stroke, and heart failure. Objective: This systematic review aims to summarize the structural, functional, and molecular changes associated with cardiovascular aging. Methods: A systematic review was conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The keywords used were (“cardiac aging” OR “aging heart” OR “cardiovascular aging”) AND (“structural” OR “functional”). Articles were selected based on inclusion criteria: original research, written in English, and published between 2020 and 2025. Exclusion criteria: limited access, duplicate publications, and articles that did not meet the PICO framework. Results: The initial search identified 822 articles. A total of 487 were excluded due to being published more than 5 years ago, 3 due to language, 131 due to duplication, 118 due to irrelevant PICO criteria, 71 for not being original research, and 7 due to limited access. The final analysis included 5 articles. Findings indicated that cardiac aging is marked by structural and functional changes such as atrial dilation, reduced ventricular elasticity, and activation of senescence-associated genes. Techniques including CMR, micro-CT, RNA sequencing, iPSC-progeria models, and fractal analysis collectively demonstrated progressive changes from the anatomical to molecular level. Conclusion: Cardiovascular aging involves integrated changes in cardiac structure, function, and molecular regulation. The integration of imaging, molecular, and cellular approaches enables the identification of potential biomarkers and the development of more targeted interventions to slow cardiovascular aging in the elderly.